Alpha-1 antitrypsin governs alcohol-related liver disease in mice and humans. Issue 3 (22nd July 2020) - Grander, Christoph; Schaefer, Benedikt; Schwärzler, Julian; Grabherr, Felix; de Graaf, Dennis M; Enrich, Barbara; Oberhuber, Georg; Mayr, Lisa; Sangineto, Moris; Jaschke, Nikolai; Adolph, Timon E; Effenberger, Maria; et al.
Abstract : Objective: Alcohol-related liver disease (ALD) is a global healthcare problem with limited treatment options. Alpha-1 antitrypsin (AAT, encoded by SERPINA1 ) shows potent anti-inflammatory activities in many preclinical and clinical trials. In our study, we aimed to explore the role of AAT in ALD. Design: An unselected cohort of 512 patients with cirrhosis was clinically characterised. Survival, clinical and biochemical parameters including AAT serum concentration were compared between patients with ALD and other aetiologies of liver disease. The role of AAT was evaluated in experimental ALD models. Results: Cirrhotic ALD patients with AAT serum concentrations less than 120 mg/dL had a significantly higher risk for death/liver transplantation as compared with patients with AAT serum concentrations higher than 120 mg/dL. Multivariate Cox regression analysis showed that low AAT serum concentration was a NaMELD-independent predictor of survival/transplantation. Ethanol-fed wild-type (wt) mice displayed a significant decline in hepatic AAT compared with pair-fed mice. Therefore, hAAT-Tg mice were ethanol-fed, and these mice displayed protection from liver injury associated with decreased steatosis, hepatic neutrophil infiltration and abated expression of proinflammatory cytokines. To test the therapeutic capability of AAT, ethanol-fed wt mice were treated with human AAT. Administration of AAT ameliorated hepatic injury, neutrophil infiltration and steatosis. Conclusion: Cirrhotic ALD patients with AAT concentrations less than 120 mg/dL displayed an increased risk for death/liver transplantation. Both hAAT-Tg mice and AAT-treated wt animals showed protection from ethanol-induced liver injury. AAT could reflect a treatment option for human ALD, especially for alcoholic hepatitis.